Enhanced decoupled current control with voltage compensation for modular multilevel converter (MMC) based STATCOM - Abdurrahman Umar Lawan; Haider A.F. Almurib; Jeen G. Khor (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This paper presents the application of modular multilevel converter (MMC) as a static compensator (STATCOM) for reactive current control. The current control is mostly achieved using proportional controller, proportional-integral (PI) controller, and hysteresis controller among others. PI controllers have the advantage of low harmonics and small variations.  However, due to the PI controller’s dependency on the system parameters and also due to the variations within the MMC during capacitors voltage control, variation in the MMC performance during the STATCOM non-ideal operations occur. To mitigate this, an improved performance of MMC will be presented using vector-based compensation concept. The proposed control will be introduced to depress the effect of the dynamics of the MMC based STATCOM non-ideal variations considering the impact of the voltage disturbance. This will be achieved by the introduction of voltage variables to subtract the transient variations from PI controllers’ outputs at the grid-interface; thus, improving the performance.